Genetic and regulatory architecture of Alzheimer's disease in the APOE region - Alexander M. Kulminski (Alzheimer’s & Dementia: Diagnosis, Assessment & Disease Monitoring, 2020)
Abstract Introduction Apolipoprotein E (APOE) ε2 and ε4 alleles encoded by rs7412 and rs429358 polymorphisms, respectively, are landmark contra and pro “risk” factors for Alzheimer's disease (AD). Methods We examined differences in linkage disequilibrium (LD) structures between (1) AD‐affected and unaffected subjects and (2) older AD‐unaffected and younger subjects in the 19q13.3 region harboring rs7412 and rs429358. Results AD is associated with sex‐nonspecific heterogeneous patterns of decreased and increased LD of rs7412 and rs429358, respectively, with other polymorphisms from five genes in this region in AD‐affected subjects. The LD patterns in older AD‐unaffected subjects resembled those in younger individuals. Polarization of the ε4‐ and ε2 allele–related heterogeneous LD clusters differentiated cell types and implicated specific tissues in AD pathogenesis. Discussion Protection and predisposition to AD is characterized by an interplay of rs7412 and rs429358, with multiple polymorphisms in the 19q13.3 region in a tissue‐specific manner, which is not driven by common evolutionary forces.